Poly-phase signal generation and optimizationof LPI Radar: A new approach - Kamble, Jayshree; A Pasha, I; Madhavilatha, M (International Journal of Engineering and Technology, 2018)
Low Probability of Intercept (LPI) Radar own certain positive characteristics make them nearly undetectable by Intercept Receivers. In a battle field, this present a considerable strategic problem. New digital receivers required complex signal processing techniques to detect these types of Radar. This paper address the problem of constructing a new hybrid waveform design using Poly-Phase modulation technique to optimize the detection performance of LPI Radar. Phase coded Pulse compression waveforms using Frequency Hopping Spread Spectrum (FHSS) are designed to evaluate the detection performance of LPI radar in terms ofÂ Discrimination factor (DF).The difference in DF of the Poly-phase coded and Binary phase coded signals is increasing with the increase in the phase values.The effect of noise on Hybrid Poly-Phase waveforms examined using the signal to noise ratios of -10dB,-15dB and -20dBÂ and extract the parameter necessary for the LPI Radar system.Â